Plasma cell infiltration and treatment effect in breast cancer patients treated with neoadjuvant chemotherapy - Asumi Sakaguchi; Yoshiya Horimoto; Hiroko Onagi; Daiki Ikarashi; Takayuki Nakayama; Tetsuya Nakatsura; Hideo Shimizu; Kuniaki Kojima; Takashi Yao; Toshiharu Matsumoto; Kanako Ogura; Shigehisa Kitano (Breast Cancer Research, 2021)
Abstract Background Tumour-infiltrating lymphocyte (TIL)-high breast tumours have a high rate of pathological complete response (pCR) with neoadjuvant chemotherapy. In our routine pathological diagnoses of biopsy specimens from pCR cases, we have observed a high infiltration of plasma cells (PCs). A positive correlation of PCs with favourable patient outcome has recently been reported, but little is known about how PCs contribute to local tumour immunity. Methods We retrospectively examined biopsy specimens from 146 patients with invasive breast cancer who received neoadjuvant chemotherapy. CD138+ PC infiltration was assessed by immunohistochemistry. Multiplexed fluorescent immunohistochemistry (mfIHC) with T and B cell markers was also conducted to elucidate the profile of immune cells. Results Greater PC infiltration was observed in the pCR group (p = 0.028) and this trend was confirmed in another patient cohort. With mfIHC, we observed significantly more CD8+, T-bet+CD4+, and CD8+FOXP3+ T cells, total B cells and PCs in pCR cases. Such cases were also characterised by high expression of both PD-1 and PD-L1 on B cells and PCs. In patients with hormone receptor-negative tumours, high PC infiltration was correlated with significantly longer disease-free survival (p = 0.034). Conclusions We found that higher PC infiltration in biopsy specimens before neoadjuvant chemotherapy was associated with pCR. With mfIHC, we also revealed that the local cytotoxic immune response was clearly enhanced in pCR cases, as was the infiltration of B cells including PCs. Moreover, higher PC levels were correlated with favourable outcomes in hormone receptor-negative breast cancer patients.